Biomanufacturing evolution from conventional to intensified processes for productivity improvement: a case study. Issue 1 (1st January 2020) - Xu, Jianlin; Xu, Xuankuo; Huang, Chao; Angelo, James; Oliveira, Christopher L.; Xu, Mengmeng; Xu, Xia; Temel, Deniz; Ding, Julia; Ghose, Sanchayita; Borys, Michael C.; Li, Zheng Jian
ABSTRACT: Process intensification has shown great potential to increase productivity and reduce costs in biomanufacturing. This case study describes the evolution of a manufacturing process from a conventional processing scheme at 1000-L scale (Process A, n = 5) to intensified processing schemes at both 1000-L (Process B, n = 8) and 2000-L scales (Process C, n = 3) for the production of a monoclonal antibody by a Chinese hamster ovary cell line. For the upstream part of the process, we implemented an intensified seed culture scheme to enhance cell densities at the seed culture step (N-1) prior to the production bioreactor (N) by using either enriched N-1 seed culture medium for Process B or by operating the N-1 step in perfusion mode for Process C. The increased final cell densities at the N-1 step allowed for much higher inoculation densities in the production bioreactor operated in fed-batch mode and substantially increased titers by 4-fold from Process A to B and 8-fold from Process A to C, while maintaining comparable final product quality. Multiple changes were made to intensify the downstream process to accommodate the increased titers. New high-capacity resins were implemented for the Protein A and anion exchange chromatography (AEX) steps, and the cation exchange chromatography (CEX) step was changed from bind-elute to flow-through mode for the streamlined Process B. Multi-column chromatography was developed for Protein A capture, and an integrated AEX-CEX pool-less polishing steps allowed semi-continuous Process C with increased productivity as well as reductions in resin requirements, buffer consumption, and processing times. A cost-of-goods analysis on consumables showed 6.7–10.1 fold cost reduction from the conventional Process A to the intensified Process C. The hybrid-intensified process described here is easy to implement in manufacturing and lays a good foundation to develop a fully continuous manufacturing with even higher productivity in the future.